Midwives' views and experiences of maternity care during COVID-19 in Ireland: A qualitative descriptive study - Panda, Sunita (My University, 2025)
Objective: To explore and describe midwives’ views and experiences of maternity care during the COVID-19 pandemic in Ireland. Design: A qualitative descriptive study involving semi-structured interviews to gather data was undertaken. Interviews, which were held between September 2022 and January 2023, were digitally recorded and transcribed verbatim. Thematic analysis was used to analyse the data. Setting & participants: The study setting was a large urban maternity unit (> 8000 births per year) in the Republic of Ireland. Midwives of any grade, who were involved in providing maternity care to women and their families in any area of the hospital during the pandemic were eligible for inclusion. Midwives were invited to take part via the hospital intranet and advertisements that were posted on notice boards throughout the study site. Findings: Thirteen midwives took part in the study. Four major themes reflective of midwives’ views and experiences were identified. These were: ‘Ever-evolving goalposts’, ‘Feeling vulnerable’, ‘Changing relationships’ and ‘Challenges to the Philosophy of Midwifery’. Key conclusions and implications for practice: This study highlights the need to consider the impact of COVID-19 on midwives and maternity services now and in the future. As a priority, embedding strategies to support midwives to regain and sustain psychological and physical well-being, are required. Attending to these factors may aid in sustainable retention of the midwifery workforce, and, ultimately, act as protective factors for crises that could emerge, potentially, in the future.
PUBLISHED
Keywords: COVID-19; Maternity care; Midwives’ experiences; Qualitative enquiry; Qualitative descriptive study